Elasmobranch-associated microbiota: a scientometric literature review - Correia Costa,Ivana; Amorim de Oliveira,Mariene; Wosnick,Natascha; Ann Hauser-Davis,Rachel; Siciliano,Salvatore; Nunes,Jorge Luiz Silva (PeerJ, 2022)
Elasmobranchs provide greatly relevant ecosystem services for the balance of the environments in which they are inserted. In recent decades, sharp population declines have been reported for many species in different regions worldwide, making this taxonomic group currently one of the most threatened with extinction. This scenario is almost entirely due to excessive fishing pressure, but any contributing factor that may cause additional mortality to populations must be mapped and monitored. In a fast-changing world, emerging marine pollution associated with climate change display the potential to increase the spread of infectious agents. These can, in turn, lead to mortality events, both directly and indirectly, by reducing immune responses and the physical and nutritional condition of affected individuals. In this context, the present study aimed to analyze data concerning elasmobranch-associated microbiota, identifying study trends and knowledge gaps in order to direct future studies on this topic of growing relevance for the health of wild populations, as well as individuals maintained in captivity, considering the zoonotic potential of these microorganisms.
Keywords: Bacteria; Fungi; Sharks; Batoids